1982
DOI: 10.2337/diacare.5.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Kinetics and Biologic Effects of Subcutaneously Injected Insulin Preparations

Abstract: This paper describes systematic studies on the absorption kinetics of exogenous insulin from its subcutaneous tissue depot in 52 male nonobese volunteers (age 20-30 yr). Five experimental protocols were used: effect of changing injection site, effect of temperature change and local massage, effect of aprotinin and human serum, effect of mixing regular insulin with long-acting insulin preparations, and effect of temperature change, muscular exercise, and local massage on the absorption of long-acting insulin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
128
1
6

Year Published

1983
1983
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(146 citation statements)
references
References 0 publications
11
128
1
6
Order By: Relevance
“…7 However, no differences in insulin absorption were found between superficial and deep subcutaneous adipose tissue. 12,13 It has been shown that the subcutaneous absorption of insulin varies according to adipose tissue depots, in nondiabetic 14 and diabetic 12,13,15 subjects. These differences have been found to correlate with blood flow in some studies [16][17][18][19] but not others.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, no differences in insulin absorption were found between superficial and deep subcutaneous adipose tissue. 12,13 It has been shown that the subcutaneous absorption of insulin varies according to adipose tissue depots, in nondiabetic 14 and diabetic 12,13,15 subjects. These differences have been found to correlate with blood flow in some studies [16][17][18][19] but not others.…”
Section: Introductionmentioning
confidence: 99%
“…It was -and is -a 5-day programme with a carefully constructed curriculum that aims to teach people with diabetes exactly how insulin works, using well-documented physiological and pharmacological data [5]. It was designed to transfer skills of insulin manipulation and dose adjustment to the patient, using recognised principles of adult learning.…”
mentioning
confidence: 99%
“…[Diabetologia (1995) The limitations of intensive insulin therapy are mainly due to the pharmacokinetic properties of subcutaneously injected insulin, resulting in an increased frequency of hypoglycaemia [2]. Whereas avoiding hypoglycaemia with intensive insulin therapy only seems possible by raising blood glucose levels, a more physiological insulin administration might potentially reduce blood glucose without increasing the frequency of hypoglycaemia [3]. In this context, intranasal insulin administration has gained considerable interest, since after intranasal application of insulin, plasma insulin concentrations increase more rapidly and return to basal levels more quickly than after subcutaneous insulin injections [4].…”
mentioning
confidence: 99%